2019
DOI: 10.2147/ijn.s216432
|View full text |Cite
|
Sign up to set email alerts
|

<p>Intravesical delivery of rapamycin via folate-modified liposomes dispersed in thermo-reversible hydrogel</p>

Abstract: Purpose To develop an intravesical instillation system for the treatment of bladder cancer, rapamycin (Rap) was encapsulated into liposomes and then homogeneously dispersed throughout a poloxamer 407 (P407)-based hydrogel. Methods Rap-loaded conventional liposomes (R-CL) and folate-modified liposomes (R-FL) were prepared using a film hydration method and pre-loading technique, and characterized by particle size, drug entrapment efficiency, and drug loading. The cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 72 publications
0
26
0
Order By: Relevance
“…The colloidal stability of the liposomes in the PBS solution was maintained for 3 weeks; thereafter, no signs of aggregation were revealed. Based on ZP, CWS-FL had a higher negative charge than CWS-L, which might be attributed to the presence of negatively charged functional groups derived from the DP 5K F anchored on the liposome surface [19]. For CWS-PL, the ZP shifted toward a positive charge, which was clearly derived from the positively-charged Pep1.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The colloidal stability of the liposomes in the PBS solution was maintained for 3 weeks; thereafter, no signs of aggregation were revealed. Based on ZP, CWS-FL had a higher negative charge than CWS-L, which might be attributed to the presence of negatively charged functional groups derived from the DP 5K F anchored on the liposome surface [19]. For CWS-PL, the ZP shifted toward a positive charge, which was clearly derived from the positively-charged Pep1.…”
Section: Discussionmentioning
confidence: 94%
“…The intracellular delivery of different liposomes was evaluated using the 5637 and MBT2 cell lines, which were well-known FR-expressing cancer cells that have been widely used to evaluate FR targeting [19]. As shown in the flow cytometry histogram (Figure 2A), in both cells, the fluorescence peak shifted to the right owing to liposomal treatment compared to no treatment (Isotype).…”
Section: In Vitro Cellular Uptakementioning
confidence: 99%
“…FL cell uptake was 2-fold higher than that of CL, and folate receptor-mediated endocytosis was proved by a competitive assay with folic acid pretreatment. In orthotopic bladder cancer mouse model, R-FL/P407-treated groups showed enhanced in vivo anti-tumor efficacy (Yoon et al, 2019).…”
Section: Liposomes As An Alternative Strategy Against Autophagy-relatmentioning
confidence: 93%
“…Many studies confirmed that these analogs inhibit the expression of VEGF in tumor cells. Recently, several studies elicited that rapamycin and its analogs, loaded as single and in combination with other drugs onto lipid-based NPs, could be used for effective antiangiogenic therapy [92][93][94][95]. There is a piece of evidence that somatostatin receptors (SSTRs), mainly subtype 2 (SSTR2), are significantly expressed in both glioma and glioma vasculature endothelial cells.…”
Section: Lipid-based Nanoparticles For Antiangiogenic Therapymentioning
confidence: 99%